Polymer Composites Fabricated with Calcium Carbonate Recovered from Acid Mine Drainage of the Witwatersrand Eastern Basin - Recardo D. S. Khumalo; Raymond S. Mohlamonyane; Washington Mhike; Liezl Matthews; Xandri Van Niekerk; Hendrik G. Brink; Evans M. N. Chirwa (Chemical Engineering Transactions, 2025)
An environmentally benign hydrothermal urea hydrolysis method for treating acid mine drainage has been developed, enabling the recovery of the aragonite polymorph of calcium carbonate from the three basins in the Witwatersrand region (Gauteng, South Africa). Of the three basins investigated, the calcium carbonate recovered from the Eastern basin displayed the highest crystallinity and average aspect ratio when compared to the other basins. This made it an interesting candidate for the preparation of polymer composites. In this preliminary study, the aragonite particles recovered from the Eastern basin acid mine drainage (with and without the suspended solids) were incorporated at 5 wt.% into an ethylene propylene copolymer via melt compounding. The resulting composites were then investigated for their morphologies, thermal and mechanical properties to establish the influence of particles on the polymer matrix. The results showed that the particles had a heterogeneous nucleating effect on the polymer matrix. The particles imparted an improved balance of toughness and stiffness to the ethylene propylene copolymer. The study demonstrated the possible industrial utility of the calcium carbonate recovered from the acid mine drainage, thus the self-sustaining viability of the treatment method.